Harry Potter and the Chamber of Secrets - Rowling, J. K.; GrandPré, Mary (New York : Arthur A. Levine Books, 1999)
When the Chamber of Secrets is opened again at the Hogwarts School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
"Year 2"--Spine.
Sequel to: Harry Potter and the sorcerer's stone.
Sequel: Harry Potter and the prisoner of Azkaban.
Keywords: Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Fiction